The Study of Environmental Risk Role (Factors) on the Economy of Urban Communities, Case Study: Ahwaz City - sara behvandi; mohammad reza zandmoghadam; abbas arghan; zeinab kekehabadi (تحقیقات کاربردی علوم جغرافیایی)
Today, the huge economic damage of natural hazards, especially of the micro-organisms, to human societies has led the concept of economic sustainability to mitigate the effects of crises to become an important area in crisis management. The purpose of this study was to investigate the role of environmental hazards (effluents) on Ahwaz economy. This research can be considered as a type of applied-development research, and is a descriptive-analytical study in a correlation manner. The population of the study consisted of all residents of Ahwaz, in 1395, there were no more than 1302000 people. The sample size was 384, based on the Cochran formula, and randomly available. To investigate the data, the structural equation path analysis was used in Amos18 software. The results indicated that the microprocesses had an effect on the economy of Ahwaz with a coefficient of 0.31 and a significant level of 0.002. Also, the effect of fiery gradients was 0.73, and the significance level of 0.000 on the tax, the microguns, with the coefficient of influence 0.45 and the significance of 0.000 per facility, the effects of the micrographs with the coefficient of 0.55, and the significance of 0.000 on the housing, With a coefficient of influence of 0.17 and a significant amount of 0.008 on transportation. Accordingly, microblogging has the most impact on finance with a coefficient of 0.73, and transportation with a coefficient of influence of 0.17 has had the least effect.